Smaller fields, higher yields? Rethinking intervention strategies across field sizes in Nigerian rice production - Ali Ibrahim; Kazuki Saito; João Vasco Silva; Arouna Aminou; Alvari Christian Tarfa; Louis Kouadio; Thomas Awio; Audu Sale Dogo; Kalimuthu Senthilkumar (Field Crops Research, 2026)

Improving rice yield, its stability, and nutrient use efficiency in sub-Saharan Africa using good agricultural practices - Thomas Awio; Louis Kouadio; Ali Ibrahim; Aina Andriatsiorimanana; Kazuki Saito; Kalimuthu Senthilkumar (Field Crops Research, 2026)

Yield stability of four staple crops of sub-Saharan Africa: analysis of long-term trials - Thomas Awio; Kalimuthu Senthilkumar; Ali Ibrahim; Marc Corbeels; Kazuki Saito (Nutrient Cycling in Agroecosystems, 2025)

Learning from farmers' knowledge on participatory irrigation management using Q‐methodology - George Kimbowa; Joshua Wanyama; Muhmoud Mukaya; Daniel Otim; Thomas Awio; Moses Mugisha (Irrigation and Drainage, 2025)
To sustain the performance of irrigation schemes, it is important to involve all stakeholders and enhance their management capacity. Using the Q‐methodological approach, drivers of farmers' perceptions of the management of public irrigation schemes were explored, taking the Doho rice irrigation scheme as a case study. Thirty‐nine male and female scheme farmers were selected from all 11 blocks based on the total number of Q‐set items. For each participant, an after‐Q‐sort interview was conducted to verify the Q‐sorting data. Farmers perceived that the establishment of a cooperative society, rehabilitation of the scheme and implementation of punishments for water‐user fee defaulters are among the major factors in improving the performance of the scheme and thus the general increase in rice yield. However, there is a need to improve scheme performance by introducing new technology, capacity building through training and incentives. Based on the Q‐sorting data analysis, four discourses were identified and summarized: (1) paying farmers; (2) disengaged farmers; (3) maintenance farmers; and (4) accountable farmers. All these factors contribute to key management challenges and thus to scheme performance. Local knowledge of the performance of existing schemes based on farmers' experiences is instrumental in guiding policy‐making towards sustaining planned irrigation schemes and thus contributes to improved agricultural production and livelihoods.

Indigenous nutrient supply, weeding and fertilisation strategies influence on-farm N, P and K use efficiency in lowland rice - Thomas Awio; Paul C. Struik; Kalimuthu Senthilkumar; Christian O. Dimkpa; George William Otim-Nape; TjeerdJan Stomph (Nutrient Cycling in Agroecosystems, 2023)
Enhancing use efficiency of applied fertiliser increases farmers’ returns on fertiliser investment through reducing nutrient inputs and improving yields. We investigated on-farm how indigenous nutrient supply and management practices affected N, P, and K uptake, agronomic efficiency and recovery efficiency of fertiliser, and physiological efficiency of nutrients taken up, under irrigated lowland rice conditions in Uganda. Treatments included recommended agronomic practices (RAP) without fertilisation, farmers’ practice (FP), farmers’ selected intensification practice (FIP), and RAP with NPK fertilisation (RAP + NPK). Indigenous N, P, and K supply varied greatly among farmers’ fields. N, P, and K uptake were significantly higher under RAP + NPK than under RAP, FP, and FIP; however, physiological efficiency (PE; kg grain kg −1 nutrient uptake) was significantly lower under RAP + NPK by 19% (N), and 12% (P/K), due to a larger effect of NPK application on uptake than on yield, leading to higher tissue concentrations. Indigenous available N reduced apparent N recovery, and agronomic and physiological N efficiencies independent of treatment. Also, P and K PEs decreased with increasing indigenous supply. Delaying weeding beyond recommended time, in interaction with indigenous N supply, decreased agronomic N efficiency, but increased PE of N. Interaction between P rate and timing reduced its PE; K rate and weeding time interaction reduced its PE. The decrease in efficiencies at high indigenous supply and delayed weeding indicates a need for site-specific fertilisation strategies based on naturally available nutrient levels and proper weeding. Weeding and fertilisation timing directly affect nutrient use efficiency, and therefore, fertiliser use efficiency in rice production systems.